2005
DOI: 10.1111/j.1600-0609.2004.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody CL5 recognizes the amino terminal domain of human phagocyte flavocytochrome b558 large subunit, gp91phox

Abstract: Human phagocyte flavocytochrome b558 (Cytb) is a heterodimeric integral membrane protein that serves as the electron transferase of the beta-nicotinamide adenine dinucleotidephosphate, reduced (NADPH)-oxidase, an enzyme complex important in the host defense function of phagocytic cells. In this study, we report the characterization of monoclonal antibody (mAb) CL5 that is specific for the large subunit, gp91phox, of the oxidase protein. This antibody recognizes gp91phox by immunoblot analysis of membrane extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Burritt and colleagues have previously reported that mAb CL5 is specific for the large subunit of b 558 and that the CL5 epitope contains the 135 ‐DPYSVALSELGDR region of gp91 phox . The CL5 epitope 135 ‐DPYSVALSELGDR overlaps with the 143 ‐ELGDR 147 part of 143 ELGDRQNES 151 , which we found to be an important region (EC2‐2) for FACS analysis using mAb 7D5 of gp91 phox .…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Burritt and colleagues have previously reported that mAb CL5 is specific for the large subunit of b 558 and that the CL5 epitope contains the 135 ‐DPYSVALSELGDR region of gp91 phox . The CL5 epitope 135 ‐DPYSVALSELGDR overlaps with the 143 ‐ELGDR 147 part of 143 ELGDRQNES 151 , which we found to be an important region (EC2‐2) for FACS analysis using mAb 7D5 of gp91 phox .…”
Section: Discussionmentioning
confidence: 50%
“…2). We found that more than three amino acid substitutions in five amino acids approximate to the intensity of intact human gp91 phox (Table 4, numbers [19][20][21][22][23]. As the amino acid substitution rate in the four amino acids (E143, I144, Q148 and S151) increases, these chimeric expression proteins are recognized more strongly by mAb 7D5.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation